Challenges in the Commencement of Consultant Surgical Practice: A Study of Threshold Concepts in Junior Cardiothoracic Surgeons - Smith, Julian A.; Blackburn, Simon; Nestel, Debra (International Journal of Practice-based Learning in Health and Social Care, 2018)
The transition from trainee to consultant cardiothoracic surgeon may be challenging. Curricula for cardiothoracic surgical training and for the professional development of cardiothoracic surgeons need to address the issues in transition that are the most difficult. This research used threshold concepts to identify the areas within this transition that are the most problematic. Semi-structured, in-depth, face-to-face, individual interviews were conducted with 13 junior cardiothoracic surgeons (in practice for ten years or less) who were purposively recruited. Transcripts were generated from the interviews and subjected to thematic analysis. Data was independently analysed by three researchers. Problematic areas in the transition to consultant practice included: (1) taking ultimate responsibility for patient care including clinical judgment, decision-making and unsupervised operating; (2) designing a career; (3) navigating new work environments; (4) managing relationships with colleagues, trainees and other team members; (5) managing technical challenges; (6) managing the previously unseen or unexpected; and (7) coping with adverse events. Uncertainty associated with each of these challenges was the most prominent threshold concept. Successfully addressing some or all of these problematic areas resulted in (8) change as a person or surgeon that positively influenced each individual’s sense of worth and identity as a cardiothoracic surgeon. Despite the completion of surgical education and training, time and the passing of the Fellowship examination, significant challenges remain for individuals commencing cardiothoracic surgical practice. There exist further curricular opportunities for the education of senior trainees and for the professional development of junior consultant surgeons to assist in the negotiation of these challenges.